(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Health care provider perform experience in deal with chronic wound management by identifying the exact cause, location, and type of wound which must be assessed to provide appropriate care and minimize complications of wound which is essential in the current healthcare environment and for that wound assessment tools are designed to support all qualified nurses in the wound management field in delivering safe and appropriate wound care.Methodology: Longitudinal follow-up study design was adopted to conduct and accomplish the research objectives, to describe chronic wound patient demographic and health status characteristics, and to assess wound complication post - surgical intervention, a period from 9th of November 2021 until to 12th of July 2022. A non-probability (purposive) sample of (37) patients was selected, data were gathered by using assessment sheet to collect demographic data such as Age, gender, body mass index, lifestyle (which includes smoking, nutritional status; and mobility status)and a wound description data, Wound types, Type of surgery, Duration, Surgical debridement, Allergy from dressing materials, Wound location: head, chest, and abdomen, arms and legs, and back and Wound dimension.Results of the research show distribution of age group that majority (32.4%) of sample was in age group between (18 – 29) years and the lowest value of (2.7%) of the sample between age group (70 – 79) years, body mass index (BMI) finding indicates there was a high percentage (40.5%) of obese according to value (7.30), first assessment observation of wound type shows a high proportion of (62.2%) for clean wounds and (27%) for clean contaminated with mean and S.D (1.513± 0.768).Conclusion: essential of assessment tools and strict implementation is basic element for prevention of chronic wound post – operative.